IMPLEMENTASI STRATEGI PENGEMBANGAN KEPARIWISATAAN - Persari, Diana; Heriyanto, Meyzi; Yuliani, Febri (Jurnal Ilmu Administrasi Negara, 2019)
Implementation of Tourism Development Strategy. This study aims to find out, analyze and to find out the supporting and inhibiting factors that influence the Implementation of the Tourism Development Strategy of the Sultan Riau Mosque of Penyengat Island. This type of research is qualitative descriptive research. Data collection by observing interviews and documentation with selected informants consisting of the Head and Staff of the Office of Culture and Tourism, Mosque Management, Malay Customary Institution, Tourism Awareness Group and Tourists. The results of the study concluded that the implementation of the tourism development strategy of Sultan Riau Grand Mosque from program indicators, resources and procedures was not optimal because there were still inhibiting factors for the implementation of tourism development strategies such as facilities and infrastructure, budget, human resources, not optimal synergy and partnership, but still there are supporting factors that must be optimized by the Tanjungpinang City Tourism and Culture Office, the regional strategic position, the potential for cultural diversity, the development of tourist market trends, and the opening of opportunities for cooperation.